Evaluation and adoption of irrigation technologies: management-design curves for furrow and level basin systems - Santos, Francisco Lúcio (2012)
Abstract The effect of average low-quarter requirement depth of irrigation and uniformity of applied water on the estimation of inflow rate and cutoff time of furrows and level basins is evaluated, using the SRFR-surface irrigation model and different intake rate soil characteristics. The optimum inflow rate and cutoff time is dependent on the irrigation technology and infiltration characteristics. To assist in the task of on-farm water management of furrows and level basin irrigation and the engineering design and planning of these systems management, design charts are proposed that define the optimum combination of inflow rate and cutoff time, given values of required depth and uniformity of application. The charts are plots of average low-quarter requirement depth and uniformity contours on axes of inflow rate and cutoff time. The general form of the curves shows that technical trade-off between systems becomes evident as flow rates and cutoff times decline as fields are levelled to zero slope and irrigated as basins. The relative steepness and the dense nature of the level basin uniformity contour curves reflect the importance of intense management and the greater penalty for management errors with these systems as opposed to furrows.